Description of condyle trabecular bone density of hypertension patients evaluated from panoramic radiograph using software imageJ - Meyta R. Gwen; Ria N. Firman; Farina Pramanik (Journal of Dentomaxillofacial Science, 2020)
Objective: The purpose of this research is to find condyle trabecular bone density of hypertension patients evaluating from panoramic radiograph using software imageJ.Material and Methods: The type of research is descriptive using purposive sampling method, 25 panoramic radiographs of hypertension patients aged 25-45 years old are obtained. The condyle trabecular analysis is done using software ImageJ with region of interest (ROI) 50Ã—50 pixel.Results: This shows that the condyle trabecular bone density of hypertension patients evaluated from panoramic radiograph using software ImageJ in trabecular area 29.929% and marrow area 70.071%.Conclusion: This research is that the condyle trabecular on hypertension patients evaluated from panoramic radiograph using software ImageJ was decreasing.